PROPHYLAXIS OF THE PAIN OF THE SYNDROME WHEN USING REMOVABLE DENTURES - M.Ya. Nidzelsky; N.V. Tsvetkova; V.M. Sokolovskaya (Український стоматологічний альманах, 2017)
Orthopedic dental treatment can be accompanied by pain of a different nature, a violation of sensitivity and the appearance of various paresthesias (burning, itching, tingling, numbness, etc.). Dentures are an irritant for the tissues of the oral cavity, namely, its excessive pressure in certain areas of the prosthetic bed. It is well known that a large number of patients using removable dentures can not get used to them because of the pain. The basis of our research is the goal of improving the method of preventing pain syndrome with the use of removable dentures, whereby by making changes to the special preparation for prosthetics and the means of preventing inflammatory conditions, conditions are created to prevent the pain syndrome and increase the sensitivity threshold of the mucous membrane of the prosthetic field.